2016
DOI: 10.1071/aseg2016ab269
|View full text |Cite
|
Sign up to set email alerts
|

Inverting Dynamic Elastic Moduli of a Granular Pack to Get Shear Modulus of the Grain

Abstract: SUMMARYElastic moduli of rocks derived from its powder is a new concept and can be applied in practical geophysics studies. To develop this concept, we make ultrasonic velocity measurement on granular packs of quartz sand. We calculate dynamic elastic moduli from that measurement and invert afterwards to find the shear modulus of quartz. The inversion technique follows Extended Walton Model that relies on the grain's contact surface condition between infinitely rough and perfectly smooth. We use different coor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…Ultrasonic measurement is performed during the last loading phase. Using similar samples, setup and apparatus, Ahmed et al (2016) demonstrated that during unloading after a preceding loading phase, sample length does not recover its previous length. In that context, we can infer that slowly removing the top piston does not significantly change grain arrangement.…”
Section: S a M P L E P R E P A R A T I O N A N D I M A G E A C Q U mentioning
confidence: 99%
“…Ultrasonic measurement is performed during the last loading phase. Using similar samples, setup and apparatus, Ahmed et al (2016) demonstrated that during unloading after a preceding loading phase, sample length does not recover its previous length. In that context, we can infer that slowly removing the top piston does not significantly change grain arrangement.…”
Section: S a M P L E P R E P A R A T I O N A N D I M A G E A C Q U mentioning
confidence: 99%
“…Following the recommendations from Ahmed et al . (), we set key parameters that include the loading−unloading sequence and top stress level. We start our measuring sequence with a couple of loading−unloading cycles up to 2.52 MPa, and then apply a long loading tail up to 12.60 MPa (Fig.…”
Section: Experiments Set‐up and Methodologymentioning
confidence: 99%
“…Also, we maintain one scale to measure the change in length of the sample along with the increasing stress to calculate the corresponding volumetric change. Following the recommendations from Ahmed et al (2016), we set key parameters that include the loading− unloading sequence and top stress level. We start our measuring sequence with a couple of loading−unloading cycles up to 2.52 MPa, and then apply a long loading tail up to 12.60 MPa (Fig.…”
Section: E X P E R I M E N T S E T -U P a N D M E T H O D O L O G Ymentioning
confidence: 99%
See 1 more Smart Citation